2002
DOI: 10.1143/jjap.41.922
|View full text |Cite
|
Sign up to set email alerts
|

C60Monomer as an Inherently Monodisperse Standard Nanoparticle in the 1 nm Range

Abstract: The role of temperature during magnetization reversal in a thin Fe film grown on MgO has been investigated. At a microscopic level the process takes place through jumps whose amplitude M follows a power-law probability distribution: P( M) = M −α , with α = 1 at 300 K and 1.8 at 10 K. During each avalanche, thermal activation does not play a relevant role in the initial overcoming of the potential barrier and therefore the temperature-dependent amplitude probability is related to cooperative effects taking plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Appendix B describes the data inversion scheme in detail. The actual width of the Nano-DMA transfer function was evaluated semi-empirically by fitting the theoretical transfer function of Stolzenburg (1988) to the mobility spectrum of monodisperse fullerene (C 60 ) monomer which is known to have a geometrical size around 1 nm (Seol et al 2002;Tanaka and Takeuchi 2002). The result showed that the peak mobility of the fitted transfer function was 1.1 cm 2 /V-s and the width of the transfer function was 1.07 times greater than the theoretical value evaluated at the mobility.…”
Section: Activation Efficiencymentioning
confidence: 99%
“…Appendix B describes the data inversion scheme in detail. The actual width of the Nano-DMA transfer function was evaluated semi-empirically by fitting the theoretical transfer function of Stolzenburg (1988) to the mobility spectrum of monodisperse fullerene (C 60 ) monomer which is known to have a geometrical size around 1 nm (Seol et al 2002;Tanaka and Takeuchi 2002). The result showed that the peak mobility of the fitted transfer function was 1.1 cm 2 /V-s and the width of the transfer function was 1.07 times greater than the theoretical value evaluated at the mobility.…”
Section: Activation Efficiencymentioning
confidence: 99%
“…Only a detailed description of the experimental setup for particle production is given here, because detailed descriptions of the DMA and XPS measurements have been given elsewhere. [14][15][16] Figure 1 shows a schematic of the particle production apparatus. C 60 powder (99.98% purity, Matsubo) loaded in a quartz tube of approximately 15 mm inner diameter was vaporized at 420 C in the first furnace (Asahi Rika Seisakusho ARF-30K) with an N 2 gas flow at a rate of 3.0 slm (standard liters per minute) regulated using a massflow controller (MFC) under atmospheric condition.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…While polystyrene latex (PSL) spheres are widely used as standard particles for the calibration of sizes ranging from 20 nm to several micrometers, no PSL particles for calibrations smaller than 20 nm are known (Mulholland & Bauer, 2000). Recently, Tanaka and Takeuchi (2002) succeeded in measuring the size of gasborne C 60 (1.00 nm in outer diameter) using a low-pressure DMA (LPDMA), and suggested that C 60 molecules are useful as standard particles. While Mulholland and Bauer (2000) proposed that dendrimers have unique potential as standard particles for calibration in the range of 3-15 nm, the sizes of gasborne dendrimers have unfortunately not yet been successfully measured using a DMA.…”
Section: Introductionmentioning
confidence: 99%